Adhesive, method for molding high-strength steel, and high-strength steel

By using polypropylene carbonate instead of high-density polyethylene in metal powder injection molding technology, the problems of high decomposition temperature of adhesive and the introduction of impurities are solved, and the comprehensive mechanical properties of high-strength steel are guaranteed and the scope of application expansion is expanded.

CN119747644APending Publication Date: 2025-04-04SOUTHWEST TECHNICAL ENGINEERING RESEARCH INSTITUTE OF CHINA SOUTH IND GROUP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510038505.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing plastic-based adhesive skeleton components have a high decomposition temperature and are easy to introduce impurities such as carbon and oxygen, which affects the comprehensive mechanical properties of high-strength steel components injected into metal powder.

Method used

By replacing part of high-density polyethylene with polypropylene carbonate, the introduction of carbon and oxygen impurities is reduced, the shape integrity of the injection blank is ensured, and the decomposition is carried out in stages through different components to prevent impurities from entering the sintered metal matrix.

Benefits of technology

It effectively reduces the introduction of carbon and oxygen impurities, ensures the comprehensive mechanical properties of high-strength steel, and has a wide range of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747644A_ABST
    Figure CN119747644A_ABST
Patent Text Reader

Abstract

The invention relates to the field of metal powder forming, and discloses an adhesive, a forming method of high-strength steel and the high-strength steel, based on the total amount of the adhesive, the adhesive comprises 65-85 wt% of polyformaldehyde, 2-10 wt% of polypropylene carbonate, 0-10 wt% of high-density polyethylene, 1-12 wt% of stearic acid and 2-10 wt% of ethylene-vinyl acetate copolymer. Poly (propylene carbonate) is introduced into the adhesive to partially or completely replace traditional high-density polyethylene, and in the process that the adhesive and the metal powder are mixed to form the injection blank, the integrity of the shape of the injection blank can be guaranteed. And meanwhile, the pyrolysis temperature of framework components of the adhesive is reduced in the sintering process, so that introduction of oxygen elements and carbon elements in the high-strength steel is reduced, the comprehensive mechanical property of the high-strength steel is ensured, and the application range is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal powder forming, and in particular to an adhesive and a forming method of high-strength steel and the high-strength steel. Background Art

[0002] Metal powder injection molding products have the advantages of high precision and uniform structure. This technology can be used to produce metal parts with complex structures and excellent performance in large quantities and at low cost. Metal powder injection molding technology can effectively make up for the shortcomings of high-strength steel in manufacturing complex-shaped thin-walled parts and expand the application scenarios of this material.

[0003] The biggest difference between metal powder injection molding technology and traditional powder metallurgy is that a high volume fraction of adhesive is introduced into the metal powder. Currently, the commonly used adhesive systems include plastic-based, wax-based, and water-soluble adhesive systems. Among them, plastic-based adhesives are widely used due to their strong filling ability, good shape retention ability, and wide range of applications. In plastic-based adhesive systems, polymer materials such as high-density polyethylene and polypropylene are often used as skeletons to ensure the integrity of the product after degreasing. However, on the one hand, due to the high thermal decomposition temperature of such polymer materials, such as the decomposition temperature of high-density polyethylene is around 400°C; on the other hand, according to the research of Al-Salem SM, Lettieri P. Kinetic study of high density polyethylene (HDPE) pyrolysis [J]. (Chemical Engineering Research & Design, 2010, 88 (12): 1599-1606.), high-density polyethylene will introduce carbon and oxygen impurity elements into the sintered metal during the thermal decomposition process, thereby affecting the comprehensive mechanical properties of the material.

[0004] Therefore, in order to ensure the comprehensive mechanical properties of materials for metal powder injection molding, it is necessary to avoid introducing impurity elements such as carbon and oxygen as much as possible. This is a technical problem that urgently needs to be solved. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem that the existing plastic-based adhesive skeleton components have high decomposition temperatures and are easily introduced with impurity elements such as carbon and oxygen, and to provide an adhesive and a high-strength steel forming method and high-strength steel. The adhesive uses polypropylene carbonate to replace part of high-density polyethylene, which greatly reduces the introduction of carbon and oxygen impurity elements, thereby ensuring the comprehensive mechanical properties of metal powder injection molded high-strength steel components.

[0006] To achieve the above-mentioned purpose, the present invention provides an adhesive on one hand, wherein, based on the total amount of the adhesive, the adhesive comprises: 65-85wt% of polyoxymethylene, 2-10wt% of polypropylene carbonate, 0-10wt% of high-density polyethylene, 1-12wt% of stearic acid, and 2-10wt% of ethylene-vinyl acetate copolymer.

[0007] The thermal decomposition temperature of polypropylene carbonate is relatively low, about 300°C, and polypropylene carbonate has a certain shape-keeping ability. By using polypropylene carbonate to partially or completely replace high-density polyethylene, the integrity of the shape of the injection blank can be ensured in the subsequent process of mixing with metal powder to form an injection blank. During sintering, the different components of the adhesive decompose in stages (polypropylene carbonate decomposes at about 300°C, and high-density polyethylene decomposes at about 400°C), and the use of high-density polyethylene is reduced, thereby effectively preventing carbon and oxygen impurity elements from entering the sintered metal matrix, ensuring the comprehensive mechanical properties of high-strength steel, and having a wide range of applications.

[0008] The present invention has no particular requirements on the specific types of polyoxymethylene, polypropylene carbonate, high-density polyethylene, and ethylene-vinyl acetate copolymer, and any commercially available product may be used.

[0009] The weight average molecular weight of polyoxymethylene is 500,000-1,000,000.

[0010] The weight average molecular weight of polypropylene carbonate is 50,000-100,000, and the density is 1.1-1.3g / cm 3 .

[0011] The density of high-density polyethylene is 0.94-0.976g / cm 3 , the melting temperature is 150-250℃.

[0012] The melt index of ethylene-vinyl acetate copolymer is 100-200 g / 10 min.

[0013] A second aspect of the present invention provides a method for forming high-strength steel, wherein metal powder is bonded and formed using the adhesive described in the first aspect of the present invention.

[0014] Preferably, the mass ratio of the metal powder to the adhesive is 1000:85-130. Reasonable control of the ratio of the adhesive to the metal powder can further reduce the introduction of impurity elements while ensuring the comprehensive performance of high-strength steel. The mass ratio of the metal powder to the adhesive can be any value between any two of 1000:85, 1000:90, 1000:95, 1000:100, 1000:105, 1000:110, 1000:120, 1000:130.

[0015] Preferably, the forming process comprises: mixing the adhesive and the metal powder and then performing injection molding to obtain an injection blank, and degreasing the injection blank and then sintering it to obtain high-strength steel.

[0016] Preferably, the mixing is carried out in an internal mixer, and the mixing process includes:

[0017] The internal mixer is heated to 180-240° C. and mixed at a first speed for 5-20 minutes, wherein the first speed is 20-30 rpm;

[0018] Cooling to 140-180° C. and crushing at a second rotation speed, wherein the second rotation speed is lower than the first rotation speed;

[0019] After the crushing is completed, the temperature is lowered to 100-120°C, and then cooled to room temperature at a third speed, wherein the third speed is lower than the second speed. There is no special requirement for the specific values ​​of the second speed and the third speed, as long as the requirements of gradually lowering the temperature and the speed are met. By gradually lowering the speed and temperature, it is beneficial to improve the mixing uniformity of the adhesive and the metal powder, and improve the performance of the obtained high-strength steel.

[0020] Preferably, the injection temperature of the injection molding is 160-230°C, the holding pressure is 50-80MPa, and the holding time is 2-15s. The injection temperature can be any value between any two of 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, and 230°C; the holding pressure can be any value between any two of 50MPa, 60MPa, 70MPa, and 80MPa; and the holding time can be any value between any two of 2s, 5s, 8s, 10s, 13s, and 15s.

[0021] Preferably, the sintering temperature is 1100-1400°C, and the sintering time is 90-180 min. The sintering temperature can be any value between any two of 1100°C, 1120°C, 1150°C, 1170°C, 1200°C, 1250°C, 1300°C, and 1400°C, and the sintering time can be any value between any two of 90 min, 100 min, 120 min, 150 min, and 180 min.

[0022] Preferably, the degreasing temperature is 120-180° C. The degreasing agent may be oxalic acid, and the degreasing temperature may be any value between any two of 120° C., 130° C., 150° C., 160° C., and 180° C.

[0023] Preferably, the metal powder comprises high strength steel powder.

[0024] Preferably, based on the total amount of the high-strength steel powder, the high-strength steel powder includes Cr: 0.90%-1.20wt%, Ni: 1.40%-1.80wt%, Si: 0.90%-1.20wt%, Mn: 1.00%-1.30wt%, C: 0.27%-0.34wt%, S: ≤0.016wt%, P≤0.02wt%, Cu≤0.02wt%, and the balance Fe. The adhesive provided by the present invention is particularly suitable for the above-mentioned high-strength steel powder. The high-strength steel obtained therefrom has excellent strength, toughness and wear resistance, and is generally used to manufacture mechanical parts and structural parts that bear high loads and impact loads. After heat treatment, the steel can obtain high strength, good plasticity and toughness, good fatigue resistance and fracture toughness, and low fatigue crack growth rate.

[0025] The above high strength steel powder is nearly spherical powder, D 50 = 20-50μm. Within this particle size range, the metal powder can have good fluidity, uniform powder spreading, large surface area, fast reaction rate, high density and mechanical properties, and help improve mixing efficiency and product quality. When the powder particle size is too large, it will affect the mixing effect with the binder, and it is easy to form defects such as holes during the sintering process, which will deteriorate the material properties.

[0026] A third aspect of the present invention provides a high-strength steel, wherein the high-strength steel is produced by the forming method described in the second aspect of the present invention.

[0027] Compared with the prior art, the present invention has the following advantages: after the metal powder and the adhesive are mixed to form a feed material, the feed material is subjected to an injection forming process to form an injection blank; the injection blank is degreased to obtain a degreased blank; the degreased blank is sintered to form high-strength steel, wherein the adhesive used utilizes polypropylene carbonate to replace part or all of the high-density polyethylene, which can ensure the integrity of the shape of the injection blank, and at the same time, different components in the adhesive are decomposed in stages (polypropylene carbonate decomposes at about 300°C, and high-density polyethylene decomposes at about 400°C), the use of high-density polyethylene is reduced, thereby effectively preventing carbon and oxygen impurity elements from entering the sintered metal matrix, ensuring the comprehensive mechanical properties of the high-strength steel, and having a wider range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a flow chart of the forming process of the high-strength steel obtained in Example 1;

[0029] Figure 2 This is a scanning electron microscope image of the high-strength steel obtained in Example 1. DETAILED DESCRIPTION

[0030] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0031] The terms "first", "second", etc. are used to distinguish similar objects rather than to describe a specific order or sequence. It should be understood that the data used in this way are interchangeable where appropriate so that the embodiments of the present application can be implemented in an order other than those illustrated or described herein, and the objects distinguished by "first", "second", etc. are generally of the same type, and the number of objects is not limited. For example, the first object can be one or more.

[0032] In addition, the term "and / or" in the specification and claims is used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0033] In the description of the present application, unless otherwise specified, “plurality” means two or more.

[0034] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0035] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0036] The room temperature in this application refers to 20-25°C.

[0037] In the following examples and comparative examples, unless otherwise specified, the reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased from the market. If no specific conditions are indicated in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed.

[0038] In the following embodiments and comparative examples, the hardness (HV) is tested using a microhardness tester, the shrinkage ratio is tested using a vernier caliper, the tensile strength is tested using a microcomputer-controlled electronic universal tester, the yield strength is tested using a microcomputer-controlled electronic universal tester, and the elongation is tested using a microcomputer-controlled electronic universal tester.

[0039] The weight average molecular weight of polyoxymethylene is 600,000.

[0040] The weight average molecular weight of polypropylene carbonate is 70,000 and the density is 1.2 g / cm 3 .

[0041] The density of high-density polyethylene is 0.956 g / cm 3 , the melting temperature is 200℃.

[0042] The melt index of ethylene-vinyl acetate copolymer is 150 g / 10 min.

[0043] Preparation Example 1

[0044] 80 wt % of polyoxymethylene, 10 wt % of polypropylene carbonate, 8 wt % of stearic acid and 2 wt % of ethylene-vinyl acetate copolymer are mixed to obtain an adhesive, wherein the decomposition temperature of the skeleton component of the adhesive is 280° C.

[0045] Preparation Example 2

[0046] An adhesive is obtained by mixing 80 wt % of polyoxymethylene, 8 wt % of polypropylene carbonate, 2 wt % of high-density polyethylene, 8 wt % of stearic acid, and 2 wt % of ethylene-vinyl acetate copolymer.

[0047] Preparation Example 3

[0048] An adhesive is obtained by mixing 80 wt % of polyoxymethylene, 2 wt % of polypropylene carbonate, 8 wt % of high-density polyethylene, 8 wt % of stearic acid, and 2 wt % of ethylene-vinyl acetate copolymer.

[0049] Comparative Preparation Example 1

[0050] 80 wt % of polyoxymethylene, 10 wt % of high-density polyethylene, 8 wt % of stearic acid and 2 wt % of ethylene-vinyl acetate copolymer are mixed to obtain an adhesive, wherein the decomposition temperature of the skeleton component of the adhesive is 420° C.

[0051] Example 1

[0052] The preparation process of this embodiment is as follows Figure 1 As shown, the details are as follows:

[0053] S1: Mix the high-strength steel powder with the adhesive from Preparation Example 1 to form a feed material. The specific process is as follows: After the internal mixer is heated to 220°C, the high-strength steel powder and the adhesive from Preparation Example 1 are added, and the mixture is kept warm and internally kneaded for 20 minutes at a speed of 25 rpm; then the temperature is reduced to 180°C, the speed is reduced (about 15 rpm), and crushing begins; when the temperature drops to 120°C, the speed is reduced again (about 10 rpm) until the feed material is cooled to room temperature to obtain the raw material, wherein the mass ratio of the high-strength steel powder to the adhesive is 1000:100.

[0054] The high-strength steel powder includes Cr: 1.0wt%, Ni: 1.50wt%, Si: 1.12wt%, Mn: 1.2wt%, C: 0.31wt%, S: ≤ 0.01wt%, P ≤ 0.01wt%, Cu ≤ 0.01wt%, and the balance Fe, powder D 50 =23.35μm.

[0055] S2: performing injection molding to obtain an injection blank. Specifically, the raw material is placed in an injection molding machine, and injection molding is performed through a mold to obtain an injection blank. The injection parameters are: holding pressure 50 MPa, holding time 2S, and injection temperature 220°C.

[0056] S3: Degreasing the injection blank with oxalic acid using a degreasing furnace to obtain a degreasing blank, and the degreasing temperature is 150°C.

[0057] S4, sintering the degreased blank at high temperature to obtain high-strength steel, wherein the sintering temperature is 1250° C. and the sintering time is 100 min.

[0058] The scanning electron microscope image of the high-strength steel prepared in this embodiment is as follows: Figure 2 As shown, it can be seen that the final product has uniform pore distribution, small pores and good overall product quality.

[0059] Example 2-3

[0060] The process was carried out in the same manner as in Example 1, with the only difference being that the adhesives used in Examples 2-3 were from Preparation Examples 2 and 3, respectively.

[0061] Example 4

[0062] The method of Example 2 was followed, except that the process parameters of injection molding were different, specifically as follows: holding pressure 80 MPa, holding time 15 s, injection temperature 180°C.

[0063] Example 5

[0064] The process was carried out in the same manner as in Example 2, except that the process parameters of injection molding were different, specifically as follows: holding pressure 100 MPa, holding time 1 S, injection temperature 240°C.

[0065] Example 6

[0066] The method of Example 2 was followed, except that the process parameters of injection molding were different, specifically as follows: holding pressure 20 MPa, holding time 30 s, injection temperature 180°C.

[0067] Example 7

[0068] The method of Example 2 is followed, except that the sintering process parameters are different, specifically as follows: the sintering temperature is 1100° C., and the sintering time is 150 min.

[0069] Example 8

[0070] The method of Example 2 is followed, except that the sintering process parameters are different, specifically as follows: the sintering temperature is 1100° C., and the sintering time is 180 min.

[0071] Example 9

[0072] The method of Example 2 is followed, except that the sintering process parameters are different, specifically as follows: the sintering temperature is 1400° C., and the sintering time is 120 min.

[0073] Comparative Example 1

[0074] The process was carried out in the same manner as in Example 1, except that the adhesive was from Comparative Preparation Example 1.

[0075] The high-strength steels prepared in the above-mentioned Examples 1-9 and Comparative Example 1 were subjected to performance tests, and the results are shown in Table 1.

[0076] Table 1 Performance test results

[0077]

[0078] As can be seen from Table 1, in Examples 1-3, as the proportion of polypropylene carbonate decreases and the proportion of high-density polyethylene increases, the hardness, yield strength and tensile strength of the product gradually increase, but the extension increases first and then decreases. This is mainly due to the increase in the content of high-density polyethylene, which will increase the thermal decomposition temperature of the adhesive skeleton component, and the carbon and oxygen elements in its pyrolysis products are easy to enter the sintered metal matrix. Studies have shown that although the introduction of carbon and oxygen elements can improve the strength of the final sintered product, the room temperature plasticity (elongation reduction) of the final sintered product will be degraded. At the same time, the introduction of too much carbon and oxygen elements into the sintered metal matrix may also make it brittle, seriously affecting the use of the final sintered product. In addition, in Example 1, since high-density polyethylene is not used at all, it is difficult for the sample to form a continuous and complete degreasing channel during the degreasing process, so that the degreasing rate of the degreasing blank is not up to standard. Excessive residues of adhesives are prone to introduce defects such as bulges during the sintering process, affecting the dimensional accuracy and mechanical properties of the final sintered product. Therefore, the amount of polypropylene carbonate and high-density polyethylene needs to be controlled within an appropriate range to obtain a high-strength steel product with better comprehensive performance.

[0079] To this end, the present application also particularly provides a more preferred embodiment, which is as follows: based on the total amount of the adhesive, the adhesive includes: 78-82wt% of polyoxymethylene, 2-8wt% of polypropylene carbonate, 2-8wt% of high-density polyethylene, 6-10wt% of stearic acid, and 1-3wt% of ethylene-vinyl acetate copolymer;

[0080] The forming method comprises: mixing metal powder and adhesive and then performing injection molding to obtain an injection blank, degreasing the injection blank and then sintering it to obtain high-strength steel, wherein the mass ratio of the metal powder to the adhesive is 1000:95-105, the injection temperature of the injection molding is 220-230°C, the holding pressure is 50-80MPa, the holding time is 2-15s, the sintering temperature is 1250-1400°C, and the time is 150-180min.

[0081] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any appropriate manner. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations. However, these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An adhesive, characterized in that: Based on the total amount of the adhesive, the adhesive includes: 65-85wt% of polyoxymethylene, 2-10wt% of polypropylene carbonate, 0-10wt% of high-density polyethylene, 1-12wt% of stearic acid, and 2-10wt% of ethylene-vinyl acetate copolymer.

2. A method for forming high-strength steel, characterized in that: The metal powder is bonded and molded using the adhesive according to claim 1.

3. The forming method according to claim 2, wherein: The mass ratio of the metal powder to the adhesive is 1000:85-130.

4. The forming method according to claim 2 or 3, wherein: The forming process includes: mixing the adhesive and the metal powder and then performing injection molding to obtain an injection blank, degreasing the injection blank and then sintering it to obtain high-strength steel.

5. The forming method according to claim 4, wherein: The mixing is carried out in an internal mixer, and the mixing process includes: The internal mixer is heated to 180-240° C. and mixed at a first speed for 5-20 minutes, wherein the first speed is 20-30 rpm; Cooling to 140-180° C. and crushing at a second rotation speed, wherein the second rotation speed is lower than the first rotation speed; After the crushing is completed, the temperature is lowered to 100-120° C., and then cooled to room temperature at a third rotation speed, wherein the third rotation speed is lower than the second rotation speed.

6. The forming method according to claim 5, wherein: The injection molding process has an injection temperature of 160-230°C, a holding pressure of 50-80 MPa, and a holding time of 2-15 seconds. And / or, the sintering temperature is 1100-1400° C. and the sintering time is 90-180 min.

7. The forming method according to claim 5 or 6, wherein: The degreasing temperature is 120-180°C.

8. The forming method according to any one of claims 2 to 7, wherein: The metal powder includes high strength steel powder.

9. The forming method according to claim 8, wherein: Based on the total amount of the high-strength steel powder, the high-strength steel powder includes Cr: 0.90%-1.20wt%, Ni: 1.40%-1.80wt%, Si: 0.90%-1.20wt%, Mn: 1.00%-1.30wt%, C: 0.27%-0.34wt%, S: ≤0.016wt%, P≤0.02wt%, Cu≤0.02wt%, and the balance Fe.

10. A high strength steel, characterized in that: The molding method according to any one of claims 2 to 9 is obtained.